1975
DOI: 10.1071/bi9750189
|View full text |Cite
|
Sign up to set email alerts
|

Basic Studies relating to the Transference of Genetic Characters From Triticum Monococcum L. to Hexaploid Wheat

Abstract: Two techniques used for genetic transfer of stem rust resistance from einkorn (T. monococcum) to hexaploid wheat are described. Success of direct interspecific hybridization between wheat and einkorn was confined to the wild form, and is attributed to differences in survival and development of F 1 hybrids rather than crossability between the two species or germination of hybrid grains. Meiotic pairing between A genome chromosomes in interspecific hybrids was shown to be significantly lower in AABD than in AAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 8 publications
2
12
0
1
Order By: Relevance
“…The suppression of resistance to cereal rusts carried by H. chilense seems rather lo be due to intergenomic interaction. Similar cases of suppression of resistance have been described in cereal amphiploids (Quinones e( at,, 1972;The & Baker, 1975;Kerber & Green, 1980;Kerber, 1983;Chevre et at,, 1989) as well as in barley addition lines in wheat (Shepherd & Johnson, 1982). Nevertheless, H, chitense resistance to Septoria tritici (Rubiales et at,, 1992a), to Erysiphe graminis (D.R.. unpublished data) and to Metoidogyne naasi (Person-Dedry \ er et at,, 1990) is expressed in tritordeum and there is a dilution of resistance at higher ploidy levels.…”
Section: Discussionsupporting
confidence: 56%
“…The suppression of resistance to cereal rusts carried by H. chilense seems rather lo be due to intergenomic interaction. Similar cases of suppression of resistance have been described in cereal amphiploids (Quinones e( at,, 1972;The & Baker, 1975;Kerber & Green, 1980;Kerber, 1983;Chevre et at,, 1989) as well as in barley addition lines in wheat (Shepherd & Johnson, 1982). Nevertheless, H, chitense resistance to Septoria tritici (Rubiales et at,, 1992a), to Erysiphe graminis (D.R.. unpublished data) and to Metoidogyne naasi (Person-Dedry \ er et at,, 1990) is expressed in tritordeum and there is a dilution of resistance at higher ploidy levels.…”
Section: Discussionsupporting
confidence: 56%
“…Interaction between the genomes in allopolyploid wheat is associated with the reduction or loss (suppression) of resistance to fungal plant pathogens causing stem rust [11][12][13] , leaf rust 11,14,15 , stripe rust 16 , and powdery mildew 17,18 . One constraint in wheat breeding is the suppression of stem rust resistance (Sr) genes when transferred from diploid and tetraploid ancestors to hexaploid wheat [11][12][13][14][15][19][20][21][22] . Suppression of stem rust resistance was first reported in 1980 when it was discovered that the loss of the D genome chromosomes activated resistance to several Pgt races that were virulent to the hexaploid wheat cultivar "Canthatch" (CTH) 23 .…”
mentioning
confidence: 99%
“…The failure of the substitution line to locate the gene in accession 104 on chromosome 1A could be attributed to a suppressor gene present in the D-genome chromosome of the substitution line 1D1A. There are reports indicating that substituted Dgenome of wheat may affect expression of leaf rust resistance genes present on the A-or B-genomes (The & Baker, 1975;Kerber, 1983;Dyck, 1987;Bai & Knott, 1992). Konzak & Joppa (1988) further demonstrated that the D-genome chromosomes in the substitution Table 4.…”
Section: Discussionmentioning
confidence: 90%